The effect of carrier microstructure on bioactivities of covalently bound osteogenic-related peptides in vivo. (December 2022) - Du, Zhipo; Wang, Cunyang; Chen, Ying; Guo, Qi; Zhang, Ke; Di, Yuntao; Li, Xiaoming
Graphical abstract: The ectopic osteogenesis and bone repair ability in vivo of two types of osteogenic-related peptides covalently bound with functionalized carbon nanotubes and graphene were systematically studied to explore the effects of carrier microstructure on bioactivities of covalently bound osteogenic-related peptides, and the possible mechanism was proposed. Highlights: Four chemical functional groups were successfully introduced into two kinds of differently microstructured carriers with equal grafting rate. Two types of osteogenic-related peptides were successfully covalently bound with the eight kinds of carriers with the same molar amount. It for the first time revealed that curvature of the carrier surface significantly affected bioactivities of the peptides. Positive effect order of the four covalent binding modes on bioactivities of the peptides was for the first time announced. Abstract: Covalent binding with bioactive substances is one of effective and promising strategies to improve bioactivities of artificial materials. However, there is still a lack of systematic understanding of how the microstructure of carriers affect performances of the covalently bound bioactive substances. In this study, we firstly introduced four chemical functional groups into two kinds of differently microstructured carriers, multi-walled carbon nanotubes (MWCNTs) and graphene (GP), with equal grafting rate. Then two types of osteogenic-related peptides were respectively covalently bound with the eight kinds of carriers with the same molar amount. Subsequently, performances of the MWCNTs/Peptides and GP/Peptides composites were evaluated using ectopic osteogenesis model in rats and calvarial defect model in rabbits respectively. The results showed that the ability of inducing osteogenesis and repairing bone defect of the peptides covalently bound with the MWCNTs was better than that of the peptides covalently bound with the GP, and that the positive effect order of the four covalent binding modes on bioactivities of the peptides was for the first time announced. Furthermore, the possible mechanism was proposed and discussed. Our study could provide important guidance for the research and development of high-performance tissue repair materials covalently bound with related bioactive substances.